Perceptual Errors Support the Notion of Masking by Object Substitution. (February 2019) - Pilling, Michael; Guest, Duncan; Andrews, Mark
Two experiments examined the effect of object substitution masking (OSM) on the perceptual errors in reporting the orientation of a target. In Experiment 1, a four-dot trailing mask was compared with a simultaneous-noise mask. In Experiment 2, the four-dot and noise masks were factorially varied. Responses were modelled using a mixture regression model and Bayesian inference to deduce whether the relative impacts of OSM on guessing and precision were the same as those of a noise mask, and thus whether the mechanism underpinning OSM is based on increasing noise rather than a substitution process. Across both experiments, OSM was associated with an increased guessing rate when the mask trailed target offset and a reduction in the precision of the target representation (although the latter was less reliable across the two experiments). Importantly, the noise mask also influenced both guessing and precision, but in a different manner, suggesting that OSM is not simply caused by increasing noise. In Experiment 2, the effects of OSM and simultaneous-noise interacted, suggesting the two manipulations involve common mechanisms. Overall results suggest that OSM is often a consequence of a substitution process, but there is evidence that the mask increases noise levels on trials where substitution does not occur.